Civic Education Learning in the 21st Century Skills-Based Digital Era - Saleh, Muhamad; Komalasari, Kokom; Sapriya, Sapriya; Masyitoh, Iim Siti (International Conference on Elementary Education, 2021)
The existence of Citizenship Education in the face of the development of the Industrial Revolution 4.0 era is very much in line with the current digital era, namely digital citizenship based on 21st-century skills which all lead to strengthening Pancasila and the 1945 Constitution of the Republic of Indonesia in the actions and behavior of students. The purpose of this research is to provide an overview and describe the learning model of citizenship education in the digital era and to foster a skill-based understanding of student learning literacy in the 21st century. The method used is a descriptive qualitative approach and data collection techniques using literature studies. The implication of this research is to form and have an impact on changing the competency demands of students in the 4.0 era that must be owned by the output and process of learning education, especially Citizenship Education.